Effect of organizational culture, job satisfaction and organizational citizenship behavior (OCB) on the performance of camat office employees in Sungai Penuh - Regen, Ronal; Fadhlan, Fadhlan; Pardizal, Zalmi; Hadi, Yohanes Ikhwan (Institute of Computer Science (IOCS), 2024)
Performance has a very important role because performance is a form of the final result of the process of employees completing their duties. Employees who complete their duties properly and correctly will have high performance. Organizational culture has a very important role for institutions. Organizational culture can be said to be good if it is able to influence all its members to contribute to productivity and effective performance. A good organizational culture and fulfilled employee needs will create job satisfaction and Organizational Citizenship Behavior. This study aims to see the effect of (1) organizational culture on employee performance, (2) job satisfaction on employee performance, (3) OCB on employee performance, and (4) organizational culture, job satisfaction and OCB together on employee performance. The sample in this study amounted to 32 people with the sampling technique was total sampling using multiple linear regression analysis tools. The results of this study indicate that (1) organizational culture has a positive and significant effect on performance, (2) job satisfaction has a positive and significant effect on employee performance, (3) OCB has a positive and positive effect on performance, (4) organizational culture, job satisfaction and OCB simultaneously have a positive and significant effect on performance of camat office employees in sungai penuh.